Keeping it in the family: exploring Igbo ethnic entrepreneurial behaviour in Nigeria. Issue 1 (24th September 2018) - Igwe, Paul Agu; Newbery, Robert; Amoncar, Nihar; White, Gareth R.T.; Madichie, Nnamdi O.
Abstract : Purpose: The purpose of this paper is to examine the attributes of the Igbos in Eastern Nigeria and the underlying factors influencing their entrepreneurial behaviour. More specifically, the study highlights the links between family, culture, institution and entrepreneurial behaviour in the African context. Design/methodology/approach: This paper is based on a qualitative research method by interviewing 50 entrepreneurs and community leaders of the Igbo nation. Igbos have been described as "naturally enterprising and ingenious" and can be found throughout Nigeria and West Africa. Understanding the vagaries of ethnic entrepreneurship can arguably only be achieved through research that is undertaken within these socio-historically rich, traditional and cultural contexts. Findings: Linked to the social learning theory, Igbo families provide an entrepreneurial leadership platform which influences youths through role models, providing mastery experiences and socialisation. The extended family provides a safe environment for risk taking, creativity and innovation. Also, an informal apprenticeship system provides entrepreneurial learning that prepares the younger generation to take to business as a way of life. Research limitations/implications: The study is based on a relatively small sample size of 50 respondents, which makes it difficult to generalise the findings despite the benefits of the research methods adopted in the study. Also, there are limitations to the extension of the findings to a generalised Igbo population comprising individuals who may, or may not, behave entrepreneurially. Practical implications: There are significant practical implications, both nationally and internationally, for policy makers that are concerned with developing jobs for the growing population of unemployed youths and inclusive entrepreneurship in Nigeria. Originality/value: The research has three main contributions. First, it valorises indigenous knowledge of family and institutional entrepreneurial behaviour in an African context. Second, it highlights the importance of the linked institutions of the extended family and the informal apprenticeship system in Igbo culture. Finally, it provides a model and an explanation of how the Igbo culture nurtures and develops transgenerational entrepreneurial behaviour.